2014
DOI: 10.4141/cjps-2014-131
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hard water, spray solution storage time, and ammonium sulfate on glyphosate efficacy and yield of glyphosate-resistant corn

Abstract: Mahoney, K. J., Nurse, R. E. and Sikkema, P. H. 2014. The effect of hard water, spray solution storage time, and ammonium sulfate on glyphosate efficacy and yield of glyphosate-resistant corn. Can. J. Plant Sci. 94: 1401–1405. Effects of ammonium sulfate (AMS) on reduced glyphosate rates are well documented; however, these rates are not used by farmers. Studies in 2011 and 2012 determined the effects of AMS and hard water on glyphosate applied at a field rate. AMS (0 or 2.5 L ha−1) and glyphosate (900 g a.e. h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
3
5
1
Order By: Relevance
“…Addition of NIS to weak-acid herbicides has been shown to overcome hard water antagonism by facilitating absorption as a solubilizer or partitioning sink for the herbicides (Nalewaja et al 1991), which could explain the lack of differences between hardness treatments in the present study. Similar to the present findings, Mohoney et al (2014) reported that carrier water hardness had a negligible overall effect on the efficacy of glyphosate on common ragweed ( Ambrosia artemisiifolia L.), large crabgrass ( Digitaria sanguinalis Cyperales), and pigweed species in corn crops ( Zea mays L.).…”
Section: Resultssupporting
confidence: 90%
“…Addition of NIS to weak-acid herbicides has been shown to overcome hard water antagonism by facilitating absorption as a solubilizer or partitioning sink for the herbicides (Nalewaja et al 1991), which could explain the lack of differences between hardness treatments in the present study. Similar to the present findings, Mohoney et al (2014) reported that carrier water hardness had a negligible overall effect on the efficacy of glyphosate on common ragweed ( Ambrosia artemisiifolia L.), large crabgrass ( Digitaria sanguinalis Cyperales), and pigweed species in corn crops ( Zea mays L.).…”
Section: Resultssupporting
confidence: 90%
“…This information provides applicators greater time flexibility, because changing weather conditions may require delaying the application and prolonging storage of mixtures. Although spray water pH between 7 and 8 is common in agriculture (Hem 1985) and can lead to insecticide and fungicide alkaline hydrolysis that increases over time (Etō 1974;Kuhr and Dorough 1976), spray solution storage time did not affect 2,4-D efficacy in this experiment or the efficacy of other weak acid herbicides in previous experiments Mahoney et al 2014;Stewart et al 2009). In addition, it is important to note that hard-water antagonism occurred immediately when mixing; the 0-h treatment in this experiment was mixed and applied within 1 min.…”
Section: Influence Of Spray Solution Storage Timementioning
confidence: 60%
“…In previous studies, researchers found no differences in control with premixtures of glyphosate and dicamba 24 h after mixing or glufosinate and glyphosate when spray solutions were stored up to 7 d after mixing (Stewart et al 2009). Furthermore, glyphosate efficacy was not reduced in hard water when spray solutions were stored up to 7 d after mixing with or without AMS (Mahoney et al 2014). Spray mixture storage time is variable because some applicators mix immediately before applications and others mix ahead of time or save unused mixtures for later applications.…”
Section: Introductionmentioning
confidence: 93%
“…There are several reports about differential control of weed species obtained by glyphosate combined with nitrogen fertilizers, especially in studies conducted in North America. In a weed community, the joint application of glyphosate and (NH 4 ) 2 SO 4 resulted in a 93% reduction in plant biomass, while treatments without this adjuvant reduced biomass by 77% (Mahoney et al 2014). The control of Urochloa decumbens with glyphosate was not increased by the use of (NH 4 ) 2 SO 4 , but this combination resulted in greater control in S. halepense (Carvalho et al 2012).…”
Section: Discussionmentioning
confidence: 95%